Supply Chain Management and Advanced Planning - Stadtler, Hartmut (Springer, 2017)
With a wealth of updated material, rewritten chapters and additional case studies, this fourth edition of a hugely important work gives a broad and up-to-date overview of the concepts underlying APS. Special emphasis is given to modeling supply chains and implementing APS successfully in industrial contexts. What’s more, readers’ understanding is enhanced by several case studies covering a wide range of industrial sectors. What makes this book so crucial is that Supply Chain Management, Enterprise Resources Planning (ERP), and Advanced Planning Systems (APS) are concepts that must be mastered in order to organize and optimize the flow of goods, materials, information and funds. Here, leading experts provide insights into the concepts underlying APS.